Phytochemical Composition, Antioxidant and Antibacterial Activities of Calophyllum Canum Hook. f. ex T. Anderson Extracts: Molecular Docking Insights - Mas Atikah, Lizazman; Vivien Jong, Yi Mian; Thiruventhan, Karunakaran; Yiizamy, Suffian; Nor Hisam, Zamakshshari; Asla Marleena, Nazeri; Nik Zakuan Hakim, Nik Mohd Nazri; Mohamad Izwan, Ismail; Kirnpal Kaur, Banga Singh (John Wiley & Sons, Inc, 2026)
This study investigates the phytochemical content and biological activities of the C. canum stem bark extracts, focusing on its antioxidant and antibacterial potential. The ethyl acetate extract yielded known xanthones of 1-hydroxy-7-methoxyxanthone (1), caloxanthone C (2), trapezifolixanthone (3), ananixanthone (4), euxanthone (5), gentisin (6), 2-hydroxyxanthone (7), αmangostin (9), and a novel compound, canumolactone (8). Sequential maceration using n-hexane, dichloromethane, chloroform, ethyl acetate, and methanol was conducted to assess the total phenolic content (TPC) and total flavonoid content (TFC). The ethyl acetate extract had the highest TPC (277.33 mg GAE/g), while the chloroform extract showed the highest TFC (139.56 mg QE/g). The ethyl acetate extract exhibited the strongest antioxidant activity (IC50 = 7.52 µg/mL), with a strong negative correlation (r = −0.968) between TPC and DPPH scavenging activity. Antibacterial testing against Acinetobacter baumannii revealed significant efficacy, with MIC values as low as 0.056 mg/mL. Molecular docking showed that gentisin had the highest binding energy against Penicillin-binding proteins(PBP). These findings emphasize the importance ofsolventselection in bioactive compound extraction and highlight C. canum extracts as promising sources of natural antioxidants and antibacterial agents.